When do people bet on their selves? The role of global self-concepts in decision making. Issue 5 (2nd September 2016) - Moore, Shannon M.; Behrends, Arwen A.; Mazur, Dominika; Sanbonmatsu, David M.
Abstract: Previous research suggests that behavior is generally predicted by specific self-concepts but not global self-concepts. A study was conducted to examine the conditions under which global conceptions of self are predictive of decision-making. Participants were given the opportunity to bet lottery tickets on their performance in the "Utah Challenge" competition. Both global and specific self-concepts independently predicted betting on specific known contests and betting on a contest that was unknown. Global but not specific self-concepts independently predicted betting on a multi-faceted contest. Mediation analyses suggest that self-concepts guide decisions by influencing the perceived likelihood of success. Participants' were more overconfident about their chances of winning when a task was unknown rather than familiar.